Microwave assisted metal-/oxidant-free cascade electrophilic sulfenylation/5-endo-dig cyclization of 2-alkynylanilines to generate diversified 3-sulfenylindoles. Issue 40 (4th October 2017) - Sharma, Shivani; Pathare, Ramdas S.; Sukanya,; Maurya, Antim K.; Goswami, Bhagyashree; Agnihotri, Vijai K.; Sawant, Devesh M.; Pardasani, Ram T.
Graphical abstract: Highlights: Metal-/oxidant-free approach to 3-sulfenylindoles under microwave irradiation. Use of catalytic amount of I2 and stoichiometric amount of sulfonyl hydrazides. Broad substrate scope, excellent functional group tolerance. Shorter reaction time with minimal side products. Abstract: A metal-/oxidant-free sustainable protocol for the synthesis of 3-sulfenylindoles based on electrophilic cyclization of 2-alkynylanilines has been developed under microwave irradiation. Herein, catalytic amount of iodine and stoichiometric amount of sulfonyl hydrazides were employed as catalyst and electrophiles respectively to induce the 5- endo - dig cyclization of 2-alkynylanilines. This strategy allows a wide substrate scope, demonstrates good functional group tolerance, utilizes easily available reagents and overcome multistep synthesis.